Depithers for Efficient Preparation of Sugar Cane Bagasse Fibers in Pulp and Paper Industry - Lois-Correa, J. A. (Ingeniería Investigación y Tecnología, 2012)
Among the by-products originated in the agro-industrial process of sugar cane, bagasse is one of the most relevant (Paturau, 1989). The negative influence of significant amount of pith, or parenchymatous tissue, present in sugarcane bagasse is discussed. Since this non-fibrous material does not give any desired properties in the pulp and paper, agglomerated boards and polymer productions, it is remarked the importance of its maximum removal. A brief historical review in the development of bagasse depithers and depithing systems is presented in this paper. Further results in the development of depither, named S.M. Caribe by its author, are described. The mechanical performance of first prototypes was evaluated in a test installation where vibration control values and temperatures in the upper and lower rotor bearings were monitored. For comparison it was made a vibrational analysis of other depithers that were in operation. For the technological evaluation the input capacity, the bagasse fiber quality obtained and the influence on the produced paper quality were controlled during two sugar cane crop seasons, as well. The results obtained were superior of those reached by most of depithers currently available in the market.